2018
DOI: 10.26438/ijsrpas/v6i4.2327
|View full text |Cite
|
Sign up to set email alerts
|

DFT study of L-alanines Crystal, Molecule and Three Linear Molecules for Optoelectronic Behavior

Abstract: L-alanine requires more insight in terms of the optoelectronic properties as the organic devices. For that an electronic structure of the L-alanine using the density of state (DOS) and band structure have been calculated by the density functional theory (DFT) using the plane wave method. The unit cell crystal, single molecule and hydrogen bonding approach were investigated first in this work using GGA-PAW. The molecular orbitals were also examined using BL3YP functional for the hydrogen bonding between the ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The ∆E (band energy gap) calculation was performed using the expression E LUMO -E HOMO . The Avogadro was used to prepare the input file, which is a chemical analyzer tool [21] and all the energy calculations were performed using the program named ORCA [22].…”
Section: Dft Analysismentioning
confidence: 99%
“…The ∆E (band energy gap) calculation was performed using the expression E LUMO -E HOMO . The Avogadro was used to prepare the input file, which is a chemical analyzer tool [21] and all the energy calculations were performed using the program named ORCA [22].…”
Section: Dft Analysismentioning
confidence: 99%
“…It was found that for most of the compounds, especially for ternary and quaternary semiconductors the band gaps are underestimated by GGA potential [9,10]. In the present study, for copper based quaternary compounds GGA clearly underestimates the band gaps [11][12][13]. This is because of the fact that GGA does not consider the existence of derivative discontinuity of energy with respect to the number of electrons.…”
Section: Introductionmentioning
confidence: 49%
“…This is because of the fact that GGA does not consider the existence of derivative discontinuity of energy with respect to the number of electrons. For a group of compounds which has similar generic nature, such as ZnX, CuGeX 2 and Cu 2 ZnGeX 4 , this derivative discontinuity term is almost the same [12][13][14]. Therefore, the band gap discrepancy due to the usage of GGA compared to experimental band gap values are expected to be similar for the group of similar compounds [14].…”
Section: Introductionmentioning
confidence: 99%